Study of impact of equivalent series inductance on high-speed board emissions - Li, Kang-Rong (2013)
With rapidly growing circuit density and the demand for low power supply to ICs in high-speed printed circuit board (PCB) design, board emission issues tend to seriously deteriorate the power distribution network (PDN) on PCBs. Among a variety of proposed PDN designs and guidelines, the use of edge-mounted capacitors to suppress board emissions is validated by measurements. The results demonstrated that the edge-mounted capacitors can effectively reduce the board edge emissions from a few MHz to 1 GHz. It is believed that the capacitors' inherent equivalent series inductance (ESL) limits the suppression of PDN impedance and board emissions above 1 GHz. In this paper, the impact of ESL on the board emissions will be analyzed. Simulation results show that the ESL of the edge-mounted capacitors of a few nH still provide a low PDN impedance for the power/ground plane pair. For ESL of a few uH or larger, the capacitors cannot effectively suppress the emissions and radiation. In addition, larger ESL will bring down the first board resonant frequency of the PDN impedance from above 1 GHz to few hundred MHz. Hence, a narrower frequency band with low PDN impedance.